The Effect of Corporate Governance on Earnings Management with Audit Tenure as a Moderating Variable - Hasnawati, Hasnawati; Zen, Sri Daryanti (Dinasti Publisher, 2026)
This study aims to analyze the effect of corporate governance proxied by board independence, board gender, audit committee financial expertise, and audit committee size on earnings management with audit tenure as a moderating variable in healthcare sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study employed a quantitative approach with a sample of 23 companies or 115 observations selected using purposive sampling. Data analysis was conducted using panel data regression and Moderated Regression Analysis (MRA). The results indicate that board independence, board gender, and audit committee financial expertise do not have a significant effect on earnings management. Meanwhile, audit committee size has a significant negative effect on earnings management. Audit tenure is unable to moderate the relationship between board independence, board gender, and audit committee size and earnings management. Meanwhile, audit tenure moderates the relationship between audit committee financial expertise and earnings management with a significant positive direction that is inconsistent with the research hypothesis. This study indicates that the effectiveness of corporate governance in reducing earnings management practices still depends on the quality of corporate monitoring.